Analysis of Hemoglobine Levels in Sweet Potatoes (Ipomoe Batatas) Processing for Multiparous Pregnant Women at Minasa Upa Public Health Centre of Makassar - Rismawati; Rahayu Eryanti K (Publisher Cv. Inara, 2020)
Anemia is a health problem in this world, especially in developing countries where an estimated 30% of the world population suffers from anemia. Pregnant women are the most vulnerable to malnutrition because there is an increase in nutritional needs to meet the mothers and a fetus needs during pregnancy. One of the alternatives to overcome iron deficiency anemia is the fortification of foods that are consumed by many people, namely sweet potatoes. The aims of this research was to determine the effect of consumption of sweet potatoes processing on hemoglobin levels of multiparous mothers. This research was conducted for 1 year consisting of the first stage, namely determining the research sample based on the criteria of 32 samples, the second stage was giving informed consent and determining the intervention given, the third stage with the type of research used was Quasi-Experimental research with pretest-posttest only control group design, The design was to measure the hemoglobin levels before and after the intervention giving sweet potatoes for 2 weeks in the control group and the intervention group. The fourth stage was processing the data by using the paired T-test and independent T-test. The results of statistical tests used the paired T-test showed that in the control group the value of ? = 0.005 <? = 0.05 and the intervention group ? = 0.000 <? = 0.05. And the results of statistical tests used the independent T-test obtained a value of ? = 0.008 <? = 0.05, which means that there is an influence between sweet potatoes procesing and an increase of Hb levels for multiparous pregnant women at Minasa Upa Public Health Center of Makassar.